Isolation and characterization of phage display-derived scFv antibodies against human parechovirus 1 VP0 protein - Hietanen Eero; Tripathi Lav; Brockmann Eeva-Christine; Merilahti Pirjo; Lamminmäki Urpo; Susi Petri (NATURE PORTFOLIO, 2022)
Human parechoviruses (PeVs) are common viruses that are associated with a variety of diseases from mild gastrointestinal and respiratory symptoms to severe central nervous system infections. Until now there has not been antibodies for visualizing parechovirus infection. We used E. coli recombinant PeV-A1-VP0 protein as a target in phage display single chain variable fragment (scFv) antibody library panning. Three rounds of panning allowed identification and isolation of several candidate scFv clones, which tested positive in enzyme-linked immunosorbent assay (ELISA) against VP0. Three scFv clones (scFv-55, -59 and -71) with different CDR-3 sequences were further purified and tested in ELISA, Western blot and immunofluorescence microscopy (IFA) against a set of PeV-A1 isolates and a few isolates representing PeV types 2-6. In IFA, all three scFv binders recognized twenty PeV-A1 isolates. ScFv-55 and -71 also recognized clinical representatives of PeV types 1-6 both in IFA and in capture ELISA, while scFv-59 only recognized PeV-A1, -A2 and -A6. PeV-A1-VP0 (Harris strain) sequence was used to generate a peptide library, which allowed identification of a putative unique conformational antibody epitope with fully conserved flanking regions and a more variable core VVTYDSKL, shared between the scFv antibodies. Sequencing of the VP0 region of virus samples and sequence comparisons against parechoviral sequences in GenBank revealed 107 PeV-A1, -A3, -A8, -A17, -A (untyped) sequences with this exact epitope core sequence, which was most dominant among PeV-A1 isolates. These data suggest the first-time isolation of broad range phage display antibodies against human parechoviruses that may be used in diagnostic antibody development.